Myo-Inositol 1,3-acetals as early intermediates during the synthesis of cyclitol derivatives - Gurale, Bharat P.; Sardessai, Richa S.; Shashidhar, Mysore S. (Carbohydrate Research, 2014)
Synthetic sequences starting from commercially available myo-inositol necessarily involve protection-deprotection strategies of its six hydroxyl groups. Several strategies have been developed/attempted over the last several decades leading to the synthesis of naturally occurring phosphoinositols, their analogs, and cyclitol derivatives. Of late, myo-inositol 1,3-acetals, which can be obtained by the reductive cleavage of myo-inositol orthoesters have emerged as early intermediates for the synthesis of phosphorylated and other inositol derivatives. This mini-review is an attempt to illustrate the economy and convenience of using myo-inositol 1,3-acetals as early intermediates during syntheses from myo-inositol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Acetal; Cyclitol; Inositol; Protecting group; Signal transduction

Inositol to aromatics -benzene free synthesis of poly oxygenated aromatics - Gurale, Bharat P.; Shashidhar, Mysore S.; Sardessai, Richa S.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
A method for the preparation of benzene derivatives from myo-inositol, an abundantly available phyto chemical is described. 1,3-Bridged acetals of inososes undergo step-wise elimination leading to the formation of polyoxygenated benzene derivatives. This aromatization reaction proceeds through the intermediacy of a beta-alkoxyenone, which could be isolated. This sequence of reactions starting from myoinositol, provides a novel route for the preparation of polyoxygenated benzene derivatives including polyoxygenated biphenyl. This scheme of synthesis demonstrates the potential of myo-inositol as a sustainable non-petrochemical resource for aromatic compounds. (C) 2018 Elsevier Ltd. All rights reserved.

Lithium hydride as an efficient reagent for the preparation of 1,2-anhydro inositols: does the reaction proceed through 'axial rich' conformation? - Sarkar, Nitai; Sardessai, Richa S.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Carbohydrate Research, 2018)
scyllo-Inositol derived 1,2-trans-diequatorial halohydrins can be efficiently converted to the corresponding epoxides in the presence of lithium hydride. The structure of one of the epoxides was determined by single crystal X-ray diffraction analysis. This provides a potential route for the preparation of ring modified inositol derivatives. DFT calculations suggest that this epoxide formation could be proceeding through the intermediacy of the cyclohexane ring-inverted axial-rich conformer (1,2-trans-diaxial halohydrin). This is supported by the results of DFT calculations on the formation of inositol orthoformate, where the product is locked in the axial-rich conformation, while the starting inositol has the equatorial-rich conformation.